Публичные императивы медиа: время выборов - Костенко, Н. (Социология: теория, методы, маркетинг, 2006)
The article deals with the state of Ukrainian television in the period of pre-election campaign (2005–2006). It can be characterized by mobilization of policy in the mass media market, consolidation of unifying semantic practices, and liberalization of political differences. However, the latter does not result in public discourse.